Analysis of age-related survival differences in advanced non-small cell lung cancer patients based on real-world data - Feiyang Li; Fang Li; Haowei Lu; Dong Zhao (BMC Cancer)
Abstract Objective This study investigates survival differences between elderly and younger patients with advanced non-small cell lung cancer and their relationship with multimodal treatments, aiming to inform clinical decision-making. Methods We retrospectively analyzed clinical data from 590 patients diagnosed with advanced non-small cell lung cancer between 2018 and 2024. Data included demographics, tumor characteristics, and survival outcomes. Propensity score matching was used to balance baseline characteristics, and Kaplan-Meier curves and multivariate Cox regression models assessed survival differences. Results After propensity score matching, no significant baseline differences were observed. Kaplan-Meier analysis showed median overall survival of 21 months for the ≥ 70 years group and 19 months for the < 70 years group (HR = 0.941, 95% CI 0.766–1.156, P = 0.555). Median cancer-specific survival was 21 months for the ≥ 70 years group and 17 months for the < 70 years group (HR = 0.892, 95% CI 0.716–1.112, P = 0.298). Cox regression analyses revealed that age was not an independent prognostic factor for survival. Subgroup analysis indicated potential heterogeneity in the lung metastasis subgroup (P = 0.047), but no significant interaction effects were found in other subgroups. Conclusion Elderly patients with advanced non-small cell lung cancer achieve comparable survival benefits to younger patients when treated with multimodal approaches. Age is not an independent prognostic factor. These findings support multimodal treatment strategies for elderly patients and highlight the need for further research into personalized treatment plans.